Identification of dislocations in large tetragonal hen egg-white lysozyme crystals by synchrotron white-beam topography - Tachibana, M (Journal of synchrotron radiation, 2003)
Large tetragonal hen egg-white (HEW) lysozyme crystals have been grown by a salt concentration-gradient method. The grown crystals, of thicknesses greater than 1.5 mm, were observed by means of X-ray topography using white-beam synchrotron radiation. Line contrasts clearly appeared on the Laue topographs. Extinction of the line images was observed in specific reflections. These results mean that the observed lines correspond to dislocation images. From the extinction criterion it is shown that the predominant dislocations are of screw character with <110> Burgers vectors. In addition, dislocation loops with [001] Burgers vectors have been found in a tetragonal HEW lysozyme crystal including some cracks. These results are discussed in the light of dislocation elastic energy and slip systems in the crystals